Opportunities for Young People in Developing Sharia Economics in Indonesia in the Digital Age - Rupita, Nanda Ega; Arum, Hafidza Sanshia (JAWI : Journal of Ahkam Wa Iqtishad, 2025)
This study aims to analyze the role of the younger generation in developing the digital sharia economy in Indonesia by emphasizing sharia principles, the role of digital technology, and existing opportunities and challenges. The sharia economy is based on the principles of prohibiting usury, gharar, and maysir, and emphasizes justice, transparency, and equitable distribution of wealth. These principles serve as a moral foundation and filter in utilizing technological innovations to ensure they remain in line with sharia objectives. In the context of digitalization, these principles are highly relevant because they can steer modern economic practices towards a more ethical and equitable system. The younger generation, as digital natives, have adaptive skills in using technology and great potential as agents of transformation. They not only play a role as users of Islamic digital services but also as creators of innovations such as Islamic fintech, halal digital wallets, and waqf crowdfunding. However, there are still obstacles in the form of low Islamic financial literacy, limited adaptive regulations, and public trust issues due to the prevalence of digital fraud. This study uses a qualitative descriptive method through literature review to examine the integration of the younger generation, technology, and sharia economic principles. The results show that the synergy between these three elements is key to building an inclusive, competitive, and sustainable digital sharia economic ecosystem. Thus, Indonesia has a great opportunity to emerge as the center of the global digital sharia economy in the future.